Critical Thinking through Discovery Learning - Asep Safaat; Turmudi Turmudi; Indra Suhendra (International Conference on Elementary Education, 2020)
Education in the industrial revolution era 4.0 required students to have high-level thinking skills. One of the high-level skills that must be possessed by students was critical thinking skills. This skill was one of the important skills in improving Indonesia's ranking of PISA (Program for International Student Assessment) which was still considered low so there was a need for learning models that can give effect to students' critical thinking skills. In this study, researchers used the library method as a research method. After researchers conducted a literature review from various sources, researchers found that the discovery learning model had an effective influence on students' critical thinking skills